PRENATAL DIAGNOSIS OF β-THALASSEMIAS AND HEMOGLOBINOPATHIES - Luisella Saba; Maria Cristina Rosatelli (Mediterranean Journal of Hematology and Infectious Diseases)
Prenatal diagnosis of β-thalassemia was accomplished for the first time in the 1970s by globin chain synthesis analysis on fetal blood obtained by placental aspiration at 18-22 weeks gestation. Since then, the molecular definition of the β- globin gene pathology, the development of procedures of DNA analysis, and the introduction of chorionic villous sampling have dramatically improved prenatal diagnosis of this disease and of related disorders. Much information is now available about the molecular mechanisms of the diseases and the molecular testing is widespread. As prenatal diagnosis has to provide an accurate, safe and early result, an efficient screening of the population and a rapid molecular characterization of the couple at risk, are necessary prerequisites. In the last decades earlier and less invasive approaches for prenatal diagnosis were developed . A overview of the most promising procedure will be done. Moreover, in order to reduce the choice of interrupting the pregnancy in case of affected fetus, Preimplantation or Preconceptional Genetic Diagnosis (PGD) has been setting up for several diseases including thalassemias.